CERPEN-CERPEN KOMPAS 1970—1980 DALAM HEGEMONI NEGARA ORDE BARU (ANALISIS WACANA KRITIS) - Apri Damai Sagita Krissandi (POETIKA, 2014)
0px; "> The objectives of this research are to understand the country’s hegemony in the Kompas short stories compilation,Dua Kelamin bagi Midin, and the impacts of country’s hegemony in it. This research uses a dialectic method. Thismethod has been used to analyse six short stories in the short stories compilation through social contextual aspects.This research uses Gramsci’s hegemony theory which emphasizes the importance of idea in social politics control andcritical discourse analysis to analyze text intensively through historical context. Short stories have a unique positionin its corelation to the country’s intervention in literatures. Short stories become a part of mass media or newspaperhegemonied by a country. On that position, short stories have some benefits and they are not hegemonied directly by acountry. Short stories hegemony helps mass media to balance news dealing with some mass media which get pressurefrom country. The six analyzed short stories prove that there is ideological plurality and complexity built in thecharacters relationships in the stories. It shows that there are social criticisms to the country.Keywords: hegemony, short story, Kompas, ideology